Lupus Vulgaris Leading to Extensive Nasal Deformity - Gupta, Gunjan; Sambyal, Vishal; Mahajan, Kunal; Rathour, Sanjay (International Journal of Innovative Research in Medical Science, 2017)
Case report- Lupus vulgaris(LV) is the most common variant of cutaneous tuberculosis(TB). The disease is highly prevalant among cases of secondary cutaneous TB in developing countries.[1]We report a case of extensive nasal deformity caused by lupus vulgaris, a rare presentation in modern antibiotic era. A 50 years old female presented with complaint of progressive and non- healing ulceration just below nasal tip for past 12 months. She was treated by topical and systemic antibiotics without any improvement, before being referred to our institute. The patient elicited history of erythematous lesion below nasal tip which later turned into multiple papulonodular lesions in the same area. These lesions later coalesced and ulcerated to give origin to picture at the time of presentation. On external nasal examination, columella was found to be completely eroded.(figure 1) On Anterior Rhinoscopy , the membranous and cartilaginous part of nasal septum were almost completely eroded except for some remnant of mucosa on left side (figure 2) along with serosanguinous discharge from nasal cavity. There was no cervical lymphadenopathy.Computed tomography scan showed perforation in the cartilaginous septum.(figure 3) Haematological investigations were inconclusive except for raised ESR. Histopathological features were consistent with the diagnosis of LV showing noncaseating tuberculoid granulomas and Langhan’s giant cells. Sputum for acid fast bacilli and VDRL test for syphillis were negative. Patient was put on anti- tubercular therapy for six months and was advised surgical correction after that. Unfortunately she was lost to follow up.